ESTUDO DE CASO DE PACIENTE COM GANGRENA DE FOURNIER: RELATO DE EXPERIÊNCIA - Roman, Arlete R.; Rosanelli, Cleci L. S. P.; Stübe, Mariléia; Sulcheski, Marisa L. G.; Frantz, Arlete; Dreffs, Franciele d. M. L. (Salão do Conhecimento, 2013)
Resumo